2019
DOI: 10.1101/747345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abscisic acid is essential for rewiring of jasmonic acid-dependent defenses during herbivory

Abstract: 19Jasmonic acid (JA) is an important plant hormone in the regulation of defenses 20 against chewing herbivores and necrotrophic pathogens. In Arabidopsis thaliana, the 21 JA response pathway consists of two antagonistic branches that are regulated by 22 MYC-and ERF-type transcription factors, respectively. The role of abscisic acid 23 (ABA) and ethylene (ET) in the molecular regulation of the MYC/ERF antagonism 24 during plant-insect interactions is still unclear. Here, we show that production of ABA 25 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…The role of ABA in plant immunity seems to be an ambivalent one (Ton et al, 2009 ). In some interactions, ABA can inhibit SA and JA/ET response (Lorenzo et al, 2004 ; Adie et al, 2007 ; Nahar et al, 2012 ; Hillwig et al, 2016 ), while in others it enhances JA response against fungi or herbivory (Ton and Mauch-Mani, 2004 ; Bodenhausen and Reymond, 2007 ; Ton et al, 2009 ; Liu et al, 2020b ), activating the MYC branch of JA pathway (Pieterse et al, 2011 ; Vos et al, 2019 ). In this work, the similar levels of ABA seen in both inoculated and control plants suggests it does not play a part in defense response to PWN, as it was concluded for P. pinaster response to Fusarium circinatum (Hernandez-Escribano et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ABA in plant immunity seems to be an ambivalent one (Ton et al, 2009 ). In some interactions, ABA can inhibit SA and JA/ET response (Lorenzo et al, 2004 ; Adie et al, 2007 ; Nahar et al, 2012 ; Hillwig et al, 2016 ), while in others it enhances JA response against fungi or herbivory (Ton and Mauch-Mani, 2004 ; Bodenhausen and Reymond, 2007 ; Ton et al, 2009 ; Liu et al, 2020b ), activating the MYC branch of JA pathway (Pieterse et al, 2011 ; Vos et al, 2019 ). In this work, the similar levels of ABA seen in both inoculated and control plants suggests it does not play a part in defense response to PWN, as it was concluded for P. pinaster response to Fusarium circinatum (Hernandez-Escribano et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yazawa et al (2012) found that minimizing the ABA levels in rice plants increased their resistance to Magnaporthe oryzae, the causing agent of rice blast, by impairing the pathogen penetration ability and leading to a reduction in the disease incidence. However, their inducing effect on the plant defense was also reported (Vos et al, 2019). Furthermore, ABA modulates the mycorrhizal establishment by inducing the AMF colonization at low levels but impairs it at the high ABA levels (Charpentier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the study here, not only SA and JA-Ile levels but also ABA levels were significantly higher in previously egg-laden, feeding-damaged than in egg-free, feeding-damaged plants ( Figures 4B , 7B ). ABA-mediated signaling may synergistically interact with JA-mediated plant responses to chewing insects ( Pieterse et al, 2012 ; Nguyen et al, 2016 ; Vos et al, 2019 ). Our results show that an egg-mediated increase of JA-Ile levels 3 h after the onset of feeding preceded the ABA burst after 12 h feeding upon egg-laden plants ( Figure 4B ).…”
Section: Discussionmentioning
confidence: 99%